1985
DOI: 10.1073/pnas.82.22.7490
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of a pair of prolactins released in vitro by the pituitary of a cichlid fish, Oreochromis mossambicus.

Abstract: The pituitary of the cichlid fish tilapia secretes two prolactins (PRLs) of molecular masses 20 kDa and 24 kDa. The 20-kDa PRL has an isoelectric point in the range of those of mammalian PRLs (pI 6.7), but the 24-kDa PRL is unusually basic (pI 8.7). Partial sequence information indicates that the PRLs are homologous but distinct proteins, differing by five amino acids within the first 29 NH2-terminal residues. Homology in the known region is higher with chum salmon PRL than with known mammalian PRLs. Reversed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(46 citation statements)
references
References 31 publications
(26 reference statements)
0
45
1
Order By: Relevance
“…In tilapia, Prl 177 and Prl 188 are encoded by separate genes and differ in both amino acid number and composition, and consequently exhibit only 69% homology (Specker et al 1985, Yamaguchi et al 1988, Rentier-Delrue et al 1989. While the discovery of two distinct Prl molecules in tilapia suggested the evolution of distinct actions, no clear differences in osmoregulatory action have been demonstrated (Specker et al 1985). This issue has been recently revisited by Fiol et al (2009) Early studies have shown greater RPD and Prl cell size (Dharmamba & Nishioka 1968), greater Prl cell activity (Nagahama et al 1975), and greater hypophyseal Prl content (Nicoll et al 1981) in tilapia maintained in FW compared to tilapia maintained in SW. Later, Yoshikawa-Ebesu et al (1995) reported that hyposmotically induced Prl 177 and Prl 188 synthesis is more robust in RPDs of fish acclimated to FW than in RPDs of fish acclimated to SW.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In tilapia, Prl 177 and Prl 188 are encoded by separate genes and differ in both amino acid number and composition, and consequently exhibit only 69% homology (Specker et al 1985, Yamaguchi et al 1988, Rentier-Delrue et al 1989. While the discovery of two distinct Prl molecules in tilapia suggested the evolution of distinct actions, no clear differences in osmoregulatory action have been demonstrated (Specker et al 1985). This issue has been recently revisited by Fiol et al (2009) Early studies have shown greater RPD and Prl cell size (Dharmamba & Nishioka 1968), greater Prl cell activity (Nagahama et al 1975), and greater hypophyseal Prl content (Nicoll et al 1981) in tilapia maintained in FW compared to tilapia maintained in SW. Later, Yoshikawa-Ebesu et al (1995) reported that hyposmotically induced Prl 177 and Prl 188 synthesis is more robust in RPDs of fish acclimated to FW than in RPDs of fish acclimated to SW.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent evidence suggests that this difference in responsiveness may result from the diminished capability of (Specker et al 1985, Yamaguchi et al 1988, Rentier-Delrue et al 1989. While the existence of two distinct Prl molecules, designated Prl 177 and Prl 188 , suggests an evolution of differing actions (Chen et al 1994), a bioassay failed to identify any clear differences in their osmoregulatory activities (Specker et al 1985). On the other hand, it has been reported that Prl 177 exhibits somatotropic activity while Prl 188 does not (Shepherd et al 1997).…”
Section: Journal Of Endocrinology (2012) 213 89-98mentioning
confidence: 99%
See 3 more Smart Citations